FORMULASI SEDIAAN TABLET EKSTRAK AKAR KUNING (Fibraurea tinctoria Lour.) SEBAGAI ANTIDIABETES - Hayatus Sa`adah; Supomo Supomo; Eka Siswanto; Kintoko Kintoko; Hardi Astuti Witasari (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
There are many plants that have the potential to be developed into anti-diabetic herbal medicine. One of them is yellow root (Fibraurea tinctoria Lour.) that contains chemical compounds including alkaloids, flavonoids, tannins, saponins, steroids/triterpenoids. Its known that the administration of ethanolic extract of yellow root at doses of 50, 100 and 200 mg/kg BW can reduce blood glucose levels of rats with induced with alloxan. To increase the use of yellow root in food medicine, preparations were developed by formulating the extract in tablet dosage form. In this study, tablets were made with three formulas with different fillers, namely Avicel PH 101 and pregelatinized starch. The research was conducted experimentally using three formulas with varying concentrations of fillers with a ratio between Avicel PH 101 and and pregelatinized starch, namely formula I (1:0), formula II (0.5:0,5) and formula III (0:1). Furthermore, evaluation of granules which includes evaluation of flow time, angle of repose, compressibility, mass density and moisture content. The granules were compressed and evaluated for tablets including evaluation of weight uniformity, hardness, friability and tablet disintegration time. Based on the results of the study, it can be concluded that the variation of the filler did not affect the physical properties of the yellow root extract granules, but did affect the physical properties of the tablets. The results showed that the tablet that met all the requirements for the physical properties of the yellow root extract tablet was formula II with a combination of Avicel PH 101 and Pregelatinized Starch as fillers.